Empowering Youth through Maslahat-Based Education: The Role of IPNU-IPPNU Mentoring in the Nahdlatul Ulama Family Welfare Movement in Rembang - Moh. Sugihariyadi; Moh. Sholihuddin; Muh. Misbahul Munir; M. Mahbubi; Hosaini Hosaini (STAI Hubbulwathan Duri, 2025)
This study examines the influence of the Maslahat Benefits Relations Education and IPNU-IPPNU mentoring program within the Nahdlatul Ulama’s Rembang Maslahat Family Movement. The research aims to assess how this initiative contributes to the educational and leadership development of IPNU-IPPNU cadres, grounded in the philosophical principles of Nahdlatul Ulama. A participatory community service approach was employed, engaging mentors and youth participants through interviews, surveys, and direct observation. This method facilitated active involvement and allowed for a comprehensive evaluation of the program’s outcomes. Findings demonstrate a significant improvement in participants’ leadership skills, social responsibility, and critical thinking. The mentoring program fostered a deeper alignment with Nahdlatul Ulama’s values, particularly in promoting community empowerment and collective well-being. Participants exhibited an increased capacity to implement practical leadership in real-world community settings. The mentoring initiative proved effective in developing well-rounded young leaders who not only benefit personally but also contribute to the broader community. The integration of educational theory with community service highlights the program’s dual impact—enhancing individual competence and reinforcing communal frameworks. This study underscores the importance of structured mentoring in shaping future leaders. By aligning personal development with community-based values, such programs offer a sustainable model for leadership cultivation in line with Nahdlatul Ulama’s mission.